Kekosongan Hukum dalam Pembagian Warisan 1:1 di Indonesia Perspektif Kesetaraan Gender - Nisa', Kamilatun; Tohari , Moh. Ilham (El-Ahli : Jurnal Hukum Keluarga Islam, 2025)
This article examines the legal vacuum in Indonesia’s 1:1 inheritance distribution system, particularly regarding the division of inherited assets between male and female heirs within the framework of Islamic law. The provision in the Compilation of Islamic Law (KHI), which establishes a 2:1 ratio, presents challenges when juxtaposed with the principle of gender equality as guaranteed by the 1945 Constitution and international legal instruments such as CEDAW. This study adopts a normative juridical approach with conceptual and comparative methods. The primary data consist of statutory regulations, the KHI, and other legal instruments related to inheritance systems. The data are analyzed descriptively and analytically to assess written legal norms from the perspective of gender equality and justice. The findings indicate that inheritance distribution deeds issued by notaries, as well as judicial decisions granting voluntary equal distribution among heirs, lack standardization due to the absence of a national legal framework recognizing equal distribution as a normative legal principle. This gap results in disparities across jurisdictions and creates legal uncertainty for the public. Therefore, inheritance law reform is urgently needed to provide each community group with viable legal options, ensure the legal validity of family agreements in inheritance distribution, and accommodate principles of social justice that are responsive to contemporary developments.